An Interest Stabilisation Mechanism to Unburden the ECB - Ivo Arnold (Intereconomics, 2021)
Following the twin crises of sovereign debt and COVID-19, the ECB risks being stuck in a situation of fiscal dominance, in which monetary policy is subordinated to the needs of finance ministers. A strong post-COVID-19 recovery may increase inflationary pressures, requiring a shift towards a less accommodative monetary policy stance. A tightening of monetary policy may, however, lead to a widening of interest rate spreads and new bond market tensions in the euro area. This article argues that the credibility of the ECB is undermined if it is perceived as aiming to close interest spreads. Interest spreads between euro countries arising from fiscal concerns should be a matter of fiscal policy, not monetary policy. The establishment of an interest stabilisation mechanism would allow the ECB to restore monetary dominance and to focus on maintaining price stability.
Keywords: 330; Zentralbank; Geldpolitik; Preisstabilität; EU-Staaten